Characterization and Localization of Citrullinated Proteoglycan Aggrecan in Human Articular Cartilage - Glant, Tibor T. (PLoS One, 2016)
BACKGROUND: Rheumatoid arthritis (RA) is an autoimmune disease of the synovial joints. The autoimmune character of RA is underscored by prominent production of autoantibodies such as those against IgG (rheumatoid factor), and a broad array of joint tissue-specific and other endogenous citrullinated proteins. Anti-citrullinated protein antibodies (ACPA) can be detected in the sera and synovial fluids of RA patients and ACPA seropositivity is one of the diagnostic criteria of RA. Studies have demonstrated that RA T cells respond to citrullinated peptides (epitopes) of proteoglycan (PG) aggrecan, which is one of the most abundant macromolecules of articular cartilage. However, it is not known if the PG molecule is citrullinated in vivo in human cartilage, and if so, whether citrulline-containing neoepitopes of PG (CitPG) can contribute to autoimmunity in RA. METHODS: CitPG was detected in human cartilage extracts using ACPA+ RA sera in dot blot and Western blot. Citrullination status of in vitro citrullinated recombinant G1 domain of human PG (rhG1) was confirmed by antibody-based and chemical methods, and potential sites of citrullination in rhG1 were explored by molecular modeling. CitPG-specific serum autoantibodies were quantified by enzyme-linked immunosorbent assays, and CitPG was localized in osteoarthritic (OA) and RA cartilage using immunohistochemistry. FINDINGS: Sera from ACPA+ RA patients reacted with PG purified from normal human cartilage specimens. PG fragments (mainly those containing the G1 domain) from OA or RA cartilage extracts were recognized by ACPA+ sera but not by serum from ACPA- individuals. ACPA+ sera also reacted with in vitro citrullinated rhG1 and G3 domain-containing fragment(s) of PG. Molecular modeling suggested multiple sites of potential citrullination within the G1 domain. The immunohistochemical localization of CitPG was different in OA and RA cartilage. CONCLUSIONS: CitPG is a new member of citrullinated proteins identified in human joints. CitPG could be found in both normal and diseased cartilage specimens. Antibodies against CitPG may trigger or augment arthritis by forming immune complexes with this autoantigen in the joints of ACPA+ RA patients.